Não conformidades de propriedades térmicas da NBR 15.575-4 com índices de conforto térmico adaptativo - Michel, Mariana Vallory (2019)
According to the maximum admissibility of the solar absortion of external walls (PE) for Bioclimatic Zone 8 (ZB8), the NBR 15.575-4:2013 classifies buildings with all black facades with satisfactory thermal performance for cities with hot weather, provide